STUDENTS’ PROBLEMS IN WRITING PARAGRAPH AT THE SECOND SEMESTER OF ENGLISH EDUCATION AT MUHAMMADIYAH KOTABUMI UNIVERSITY - Rulik Setiani; Dewi Sartipa; Sinta Novia (Universitas Labuhanbatu, 2023)
Writing skill is one of the most important language skill to be mastered in the language learning process, especially English. The writing process starts from writing a paragraph. Paragraph are important in writing skill. The purpose of this research was to find students’ problems in writing Paragraph and the dominant problem in Writing Paragraph at The Second Semester of English Education at Muhammadiyah Kotabumi University. This research employed descriptive qualitative research that examined 8 students in the second semester of English Education Study Program. The design of this research was descriptive qualitative research. The instrument used to collect the data were document of students writing tasks and interview guideline. The kind of interview that was used semi-structured interview. Based on theories of Bryne divides writing problems into three categories. The first is linguistic problems. Linguistic aspects such as grammar, vocabulary, Language use and choice of sentence in writing. The second is Physiology, namely content. The third is cognitive such as spelling, punctuation, capitalization and paragraph. Based on the findings, the results showed that the students' problems in writing paragraph indicate that students faced problems in 2 categories which consisted: linguistic and cognitive problems. Linguistic problems which consist of grammar is 49, vocabulary is 7, and choice of sentence is 2, and cognitive problems which consist of spelling is 1, punctuation is 26, capitalization is 29, and paragraphing is 3. Moreover, it also findthe dominant problem in writing paragraph was linguistic problems which consist grammar is 49 where student still experience problems in understanding the basic nature of grammar, namely problems in terms of the appropriateness of the placement of to be, and the correct pattern of verbs. Then, for the Physiology problem, namely content, there were no problems found on the results of the analysis of 8 students' writing documents at the second semester of English education at Muhammadiyah Kotabumi University.